Formulación del proceso agregador de valor “Graduación” para la gestión por resultados en la Unidad Educativa “Pio Jaramillo Alvarado” de la ciudad de Loja - Salazar Paz, Joseline Lissette (2023)
The primary objective of this research is to formulate a value-adding process called "Graduation" for the management by results "Pio Jaramillo Alvarado" school in the city of Loja, by developing a manual in which guidelines are provided so that high school seniors can achieve graduation and obtain their degrees according to the institution's goals. Consequently, a diagnosis was made, since the institution does not have a manual, thus, its structure is developed empirically. Additionally, the methodology applied was qualitative and descriptive. This was for the purpose of analyzing and interpreting the information obtained and identifying the main characteristics of the problem and the processes of the research topic. For the collection of information, an interview and observation form were used. This was done to determine the current situation of the process and to propose solutions to the problems encountered through action research. The methods used are of the analytical-synthetic type, thus facilitating the analysis of the information obtained and the design of a quality manual. As a result, a manual on the graduation process was prepared as a proposal to improve its development. This manual was based on standards and on the identification of the general outline of the macroprocess, as well as the design of diagrams that provide a general overview of the process. Finally, the proposal for the graduation process manual was socialized with the key actors. This manual was developed as a proposal for improving its development. In order to develop conclusions and recommendations, a discussion was held based on the results and the selected theory.